Change in muscle acitivity during skiing using 2 simulators - Taek, L. H.; Woo, K. G.; Jae, K. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This research analyzed the change in lower muscle activity during skiing using two simulators. Participants in this study were 8 male adults who held a certificate issued by the Korea Ski Instructors Association. Kinematic factors when skiing on two types of simulators were compared and analyzed. Most subjects maintained a higher value of %MVIC while repeating the positions on the Pro Ski Simulator than Skiers Edge. Efficient skiing on ski-simulators requires the maximum use of skiing time on each foot and the ability to quickly flex and extend the hip and the knee joints. Furthermore, differences between individuals exist depending on the level of ski technique and the type of simulator and it is believed that the development of an additional adjustment apparatus in the existing equipment is necessary to enable safe and effective motions.